Effect of Environmental Factors on The Relative Fitness and Spatial Distribution of Mangrove Crabs (Scylla spp) in Blok Bedul Segoro Anak, Alas Purwo National Park, Indonesia - Mahfud, Mohamad Zaenal; Sudarmadji, Sudarmadji; Subchan, Wachju (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
The mangrove forest are natural and renewable. resources Mangrove has the physical, chemicaland biological function which highly support the fulfillment of human needs and serve as a bufferbalance of the ecosystem in coastal areas. One of the functions associated with the mangrovebiological existence as a source of diversity of marine life. Marine life is affected by the presenceof mangrove forests among mangrove crab (Scylla serrata) to maintain the ecological balance andcause the energy cycle running fast. This study aims to determine the condition of environmentalfactors, the relative fitness and spatial distribution of mangrove crabin the mangrove forests BlockBedul Kali Segoro Alas Purwo National Park. Data from the study are described and classified bysimilarity of environmental factors, then performed multiple linear regression betweenenvironmental factors with relative fitness and spatial distribution of mangrove crabs. The resultsshowed that the average relative fitness mangrove crabs at all the research station is 69 with astandard deviation of 13.51. Spatial distribution of mangrove crab at any observation station isless than 1, so it can be concluded that the distribution is uniform. Environmental factors withrelative fitness mud crab significant correlation, but no significant correlation betweenenvironmental factors with the spatial distribution of mangrove crabs. Keywords: Relative Fitnes Crab Mangrove, Mangrove Crab Spatial Distribution, Alas Purwo National Park